Pemanfaatan Limbah Gergaji Kayu Mahoni (Swietenia macrophylla K.) sebagai Energi Alternatif dengan Metode Pirolisis - Asri Saleh; Hardiyanti Nur (Al-Kimia, 2018)
Abstract :The raise of materials need drives alternative new energy such as bio-oil. The sawdust of Mahagony, contained hemicelulose and lignin, was one of potential one to be alternative energy. This research aimed to define the characteristic of  sawdust  with pyrolisis method by using FTIR. The result showed that the heating effected to mass race, viscosity and calorie. The highest value of them were 1.0071 g/cm3, 1.0028 poise and 213.0956 kal/g respectively and the lowest value of them were 1.0025 g/cm3, 0.8600 poise and 13.5350 kal/g repectively. The FTIR spectrum result of Mahagony sawdust was 3426 cm -1  and 1638 cm-1 showed hydrophilic and aromatic compound.